Analisis Pola dan Ukuran Bulir Spekel menggunakan LSI (Laser Speckle Imaging) pada Lapisan Tipis TiO2: Meli Muchlian, Dahyunir Dahlan, Harmadi - Meli Muchlian, Meli Muchlian; Dahyunir Dahlan, Dahyunir Dahlan; Harmadi, Harmadi (Jurnal Fisika dan Aplikasinya, 2025)
LSI method has produced the image speckle pattern of TiO2 thin film sample. Analysis of speckle patterns and speckle grain size using autocorrelation imaging program Matlab 7 can see the changes that occur in TiO2 thin film sample due to the influence of heating temperature variation (100, 150 and 2000 C). Speckle grain size of TiO2 thin film increased due to increasing of heating temperature on the same coating number. The result of speckle pattern showed that the smallest speckle grain size counted is 45 µm and grains of TiO2 thin film is dispersed more evenly due to addition of heating temperature.